1992
DOI: 10.1152/physiologyonline.1992.7.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Role for Natriuretic Peptides in Fish Osmoregulation

Abstract: Emerging evidence indicates that atrial natriuretic peptide-like peptide hormones may play a significant role in various aspects of fish osmoregulation. Surprisingly, the bulk of current evidence supports a role in salt rather than volume regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There are several studies on the osmoregulatory actions of ANP in teleost species other than eels, the results of which are not always consistent with those of eels, as summarized in a number of reviews (23,26,51,86). Plasma ANP concentration is generally higher in SW fish than in FW fish or in euryhaline fish that are in SW than in FW (25,31,77,105).…”
Section: Osmoregulatory Actions Of Anp In Fish Other Than Eelsmentioning
confidence: 99%
“…There are several studies on the osmoregulatory actions of ANP in teleost species other than eels, the results of which are not always consistent with those of eels, as summarized in a number of reviews (23,26,51,86). Plasma ANP concentration is generally higher in SW fish than in FW fish or in euryhaline fish that are in SW than in FW (25,31,77,105).…”
Section: Osmoregulatory Actions Of Anp In Fish Other Than Eelsmentioning
confidence: 99%
“…In recent years, the biological role of NPs in the physiology of fish has received much attention and NPs have been shown to affect vascular smooth muscle and gill epithelial function in a variety of species (Evans and Takei, 1992). In elasmobranchs, highaffinity CNP receptors mediate vasodilatation in the branchial arteries of Scyliorhinus canicula (Bjenning et al, 1992) and the ventral aorta of S. acanthias (Evans et al, 1993) and potently stimulate chloride efflux from the rectal gland of S. acanthias (Solomon et al, 1992).…”
mentioning
confidence: 99%
“…LAMPREY GEOTRIA AUSTRALIS 1800 traditional view that NPs act as saltwater hormones, because the circulating NP concentrations increase during saltwater adaptation (Evans and Takei, 1992), may need to be reappraised in the light of recent data indicating that an upregulation of gill NP receptors occurs in fresh water (Katafuchi et al 1994;Takashima et al 1995;Sakaguchi et al 1996). Such findings become particularly relevant as there is now evidence that NPR-C may be linked with second messenger systems, as opposed to being a 'silent' clearance receptor present only to modulate circulating concentrations of NPs (Maack, 1992;Anand-Srivastava and Trachte, 1993).…”
Section: Natriuretic Peptide Binding Sites In the Gills Of The Pouchedmentioning
confidence: 99%
“…The discovery that a mammalian peptide system was implicated in salt and water balance suggested that NPs might play a role in fish osmoregulation (Evans, 1990). Ensuing studies quickly identified NP immunoreactivity in the heart, plasma and brain of both agnathan and gnathostome fishes and demonstrated vasodilatatory and various iono-and osmoregulatory effects (Evans and Takei, 1992). The precise actions of NPs in fish still await clarification (for general reviews, see Takei and Balment, 1993;Hagiwara et al 1995).…”
mentioning
confidence: 99%